BURNOUT SYNDROME IN MEDICAL RESIDENTS FROM MONTES CLAROS/MG - Ferreira, Emillyo César Neves (2017)
Introduction: The presence of stressor factors and the work conditions of medical residents favor the emergence of burnout syndrome, characterized by emotional exhaustion, depersonalization and decrease of professional fulfilment. Objective: Verify the relation between the Burnout syndrome and professional and socio-demographic variables in doctors from the programs of medical residences of the main hospitals in Montes Claros/MG, Brazil. Materials and methods: The Maslach Burnout Inventory was used as a research tool, along with a socio-demographic assessment form. The sample consisted of 37 residents of three hospitals in Montes Claros/MG, Brazil. Results: A high rate (75.7%) of burnout syndrome was shown among the participants, although it was not evident its relation with gender, marital status, family income or working hours. Conclusion: Nevertheless, the data reinforce the importance of preventive measures against the physical and mental exhaustion of these professionals, as demonstrated by the high prevalence identified in this study.